2016
DOI: 10.1017/s0021859616000599
|View full text |Cite
|
Sign up to set email alerts
|

Performance of crossbred dairy Friesian calves fed two levels ofSaccharomyces cerevisiae: intake, digestion, ruminal fermentation, blood parameters and faecal pathogenic bacteria

Abstract: SUMMARYThe effect of feeding two levels of Saccharomyces cerevisiae on the performance of crossbred Friesian calves was investigated. Twenty-four neonatal male Friesian × Baladi calves (35·5 ± 0·25 kg of initial body weight) were randomly assigned in a completely randomized design into three experimental groups for 90 days (eight calves per group). Calves fed their diets without yeast (S. cerevisiae) were considered as Control, while the diets of other calves were supplemented daily either with 2·5 g (YL diet)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Galvão et al () noted that the duration of diarrhoea was decreased in neonates receiving active dry yeast with feed. Similarly, Hassan et al () reported that 2·5 and 5 g of S. cerevisiae improved intake of starter diet, berseem hay and total solids in crossbred Friesian calves resulting in an increase in fermented by‐products such as VFAs as well as a decrease in the concentration/production of rumen ammonia nitrogen.…”
Section: Effect Of Feeding Single‐cell Fungi On Ruminantsmentioning
confidence: 91%
See 1 more Smart Citation
“…Galvão et al () noted that the duration of diarrhoea was decreased in neonates receiving active dry yeast with feed. Similarly, Hassan et al () reported that 2·5 and 5 g of S. cerevisiae improved intake of starter diet, berseem hay and total solids in crossbred Friesian calves resulting in an increase in fermented by‐products such as VFAs as well as a decrease in the concentration/production of rumen ammonia nitrogen.…”
Section: Effect Of Feeding Single‐cell Fungi On Ruminantsmentioning
confidence: 91%
“…Recently, supplementing live yeast in the diet of cattle grazing tropical pastures can benefit fibre‐degrading bacteria and increase fibre digestibility (Sousa et al ). Hassan et al () reported that supplementation with 2·5 and 5 g of yeast/calf increased digestion of ADF and NDF. In addition, the inclusion of 4 mg of S. cerevisiae resulted in increased dry matter degradability in sheep and steer inocula and increased degradation of organic matter in goat and sheep inocula (Vallejo‐Hernández et al ).…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 99%
“…Thus, looking for natural alternative has gained interest and importance. Phytogenic extracts (Cedillo et al, 2015), exogenous enzymes (Vallejo et al, 2016), and yeast (Hassan et al, 2016) are gaining increasing interest as feed additive for animal feeding. Such feed additives can reduce energy losses as methane (CH 4 ), and nitrogen (N) as ammonia, which reduce animal performance and contribute to the release of pollutants to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is generally recognized as safe by the Food and Drug Administration organization of USA, and it can be legally used as an animal feed additive to stabilize rumen fermentation and prevents rumen microflora disorders (Elghandour et al, 2015;Hassan et al, 2016). Yeast has the ability to modify ruminal fermentation through provision of important nutrients and nutritional cofactors required for microbial growth and activity (Polyorach et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The efficient reduction of such energy losses may be potentially used for the production of more meat and milk, rather than contributing to GHG production which impacts negatively on climate change (Eckard et al, 2010). Recently, the use of exogenous enzymes (Rojo et al, 2015) and yeast (Saccharomyces cerevisiae; SC) additives in ruminant diets has attracted considerable interest (Hassan et al, 2016). Many research studies have shown that supplementing exogenous enzymes in livestock diets improved forage quality , increase digestibility, rumen fermentation, and ruminant production (Valdes et al, 2015).…”
mentioning
confidence: 99%